2015
DOI: 10.1136/bmjopen-2015-009581
|View full text |Cite
|
Sign up to set email alerts
|

A supported psychoeducational intervention to improve family mental health following discharge from paediatric intensive care: feasibility and pilot randomised controlled trial

Abstract: ObjectiveTo assess feasibility and pilot a supported psychoeducational tool to improve parent and child mental health following discharge from a paediatric intensive care unit (PICU), in preparation for a large randomised controlled trial (RCT).DesignFeasibility assessment and single-centre, parallel group, pilot RCT. A concealed computer generated list was used to randomise participants, with an allocation of 2:1 in favour of the intervention.SettingA PICU in an acute care hospital in London, UK.Participants3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…These interventions were, however, provided at different time points, ranging from PICU admission (Melnyk et al, ) to within 7 days of discharge (Als et al . ) and 6 weeks after discharge (Gledhill et al, ) up to 2 months after discharge (Colville et al, ; Samuel et al, ) (Table ).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…These interventions were, however, provided at different time points, ranging from PICU admission (Melnyk et al, ) to within 7 days of discharge (Als et al . ) and 6 weeks after discharge (Gledhill et al, ) up to 2 months after discharge (Colville et al, ; Samuel et al, ) (Table ).…”
Section: Resultsmentioning
confidence: 88%
“…Als et al . () used an information intervention, similar to that described by Gledhill et al . () and Melnyk et al .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In children, limited evidence suggests post-traumatic stress symptoms after PICU admission, including delusional memories, intrusive thoughts, and avoidance, occur in up to 32% of PICU survivors (18,23). Septic illness, increased numbers of invasive procedures, and benzodiazepines have been implicated as risk factors (18,8992), and psychoeducational tools have been piloted with some success (12). Pediatric PICS is an important and rapidly growing area of research with results of ongoing multicenter studies expected to be published in the next few years (93).…”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%
“…Only 6 studies were identified that could be included in the review; three of these were reported as full randomized controlled trials (RCT) (35) and three as feasibility studies (68). Two of the feasibility studies also had RCT designs (6, 7) and one was an intervention without a control arm (8). Participants included parents and children.…”
Section: Editorialmentioning
confidence: 99%